Pengaruh Work Environment dan Perceived Organizational Support Terhadap Work Engagement Dimediasi oleh Self-Efficacy - Socha Safira, Astri; Prasetyoning Tyas, Ari Anggarani Winadi (Economic Reviews Journal, 2025)
The increasing complexity and dynamics of work within government institutions can affect employees’ engagement with the organization. Therefore, it is essential for institutions to understand the role of the work environment and perceived organizational support in fostering strong work engagement and enhancing employees’ self-confidence. This study aims to examine the influence of work environment and perceived organizational support on work engagement, with self-efficacy as a mediating variable among civil servants at Bappeda DKI Jakarta. The research employed a quantitative approach by distributing questionnaires to 69 employees selected through a saturated sampling technique/census. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show that the work environment positively influences self-efficacy, perceived organizational support positively affects self-efficacy, the work environment positively influences work engagement, perceived organizational support positively affects work engagement, and self-efficacy has a positive effect on work engagement. Furthermore, self-efficacy mediates the influence of both the work environment and perceived organizational support on work engagement. The study recommends that management enhance workplace comfort, encourage supportive communication from supervisors, and provide discussion and guidance when employees face new tasks. This research also contributes to the development of human resource policies, particularly in strengthening employee engagement in the public sector.